Online student attendance management system / Mohamed Razif Che Hashim - Che Hashim, Mohamed Razif (2008)
In an age of increased accountability, academic institutions face the need to manage a growing amount of student data. As a result, many of them are upgrading their student information systems (SIS) to meet specific requirements for reporting. There is, however, a large untapped benefit for faculties with regard to online student information systems - use of real-time information from the classroom to target students in need of additional assistance (intervention). Therefore, the purpose of this project is to design a web - based Online Student Attendance Management System for Universiti Teknologi MARA (UiTM). Manually, lecturers need to bring with them a piece of paper that contains information of students related to that particular class. During the class, lecturers tend to pass around a signup sheet for students to fill up the attendance details.